THE ROLE OF THE WEB-BASED DISTANCE LEARNING ENVIRONMENT IN THE EDUCATION OF FUTURE LAWYERS - Voronova, Olga V.; Filinovych, Valeriia V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of this research is the study of the essence of the web environment of distance learning and the implementation of web services and distance learning systems in the educational process of educational institutions of the country, including the Law Faculty of NAU. The methodological basis of the research comprises general-scientific and specific-scientific (i.e. special) methods. The use of these methods provided an opportunity to analyze the factors influencing the web-based distance learning environment for the training of law students. Results: based on the analysis made by the authors of the study, it is possible to conclude insufficient training of the personnel in educational institutions. A large number of low-skilled specialists are involved in the work in this field, who, even with the skills of pedagogy, do not know and do not understand information technology. The effectiveness of such training can be small, thus forming the opinion of ordinary people that distance learning will not be able to give a good result. But with the proper approach of the management of educational institutions, the situation can be corrected. To do this, it is necessary to actively implement in the educational process of distance learning systems, to hold workshops and lectures for staff, where educators will be taught to interact with the web environment for the organization of distance learning of future lawyers. Discussion: the authors suggest to improve the educational process at the Faculty of Law following the challenges and threats of today, i.e. the coronavirus pandemic, and the like. Regarding the educational training of future lawyers, it is necessary to involve world-renowned services and tools that will help make the web environment of distance learning the most favorable, transparent and understandable for every educator and student.